Assessment of competitiveness of machine-building enterprise - I.M. Teslenok; E.V. Shirokolobov (Економіка, управління та адміністрування)
One of the important characteristics of a machine-building enterprise in the context of the modern development of international market relations is the indicator of the level of competitiveness. The article reflects one of the methods of assessing the level of competitiveness of enterprises, namely the construction of competitiveness polygon, according to which the internal and overall level of competitiveness of JSC «Motor Sich» and their comparison with two main competitors – «CFM Int.» аnd «General Electric» is determined. According to the algorithm of estimation, the main competitive advantages of the organization with the help of the qualified experts of the enterprise are singled out and counted and their answers are used according to the the Kendall’s coefficient of concordance. To make a clear comparison of the numerical values of the factors of the analyzed enterprises, the polygons of competitiveness are constructed, based on which the levels of internal and external competitiveness of organizations are calculated. The obtained data are used for further correlation of the level of competitiveness of JSC «Motor Sich» with the specified competitors and their derivation in numerical value through the indicators of the relative internal and overall competitiveness of the enterprise. The results of the study make it possible to identify the weaknesses in the competitive «arms» of JSC «Motor Sich» and further develop a number of measures to fully or partially minimize these weak points. The proposed methodological approach to assess the level of competitiveness of the organization and the conclusions of the study may further be applied in determining the feasibility of changing the competitiveness management system of JSC «Motor Sich» and when looking for the ways to improve its competitiveness.